A national survey of pediatric emergency medicine physicians on improving education in child maltreatment recognition and reporting child abuse & neglect. (December 2021) - Mandadi, Akhila R.; Dully, Kathleen; Brailsford, Jennifer; Wylie, Todd; Morrissey, Thomas K.; Hendry, Phyllis; Gautam, Shiva; Fishe, Jennifer N.
Abstract: Background: Child maltreatment is an important public health problem with serious consequences. Even in the face of increased research and enhanced public awareness over the last decade, the rate of child fatalities due to reported child maltreatment has increased. Objective: This study describes pediatric emergency medicine (PEM) physicians' knowledge, training, confidence, and barriers in recognition and reporting suspected child maltreatment. Participants and setting: A nationally representative sample of PEM physician members of Pediatric Emergency Medicine Collaborative Research Committee (PEM CRC) participated. Methods: A cross-sectional 36-item survey study of PEM physicians with content domains including provider knowledge, preparedness, confidence, and barriers to identifying and reporting child maltreatment was conducted and distributed. Results: 113 of 486 members completed the survey. Confidence with recognizing and reporting child abuse (95%) was greater than in child neglect (88%). Knowledge in child maltreatment recognition and reporting was significantly correlated with confidence in reporting and recognition ( p < 0.001). There was a significant relationship between knowledge and confidence for respondents from states with training in child maltreatment recognition and reporting requirement as a condition of licensure and re-licensure compared to states without the requirement ( p < 0.01). Qualitative responses revealed insightful themes to improve child maltreatment training, recognition and reporting. Conclusion: Our national survey study demonstrates that PEM-trained physicians have high confidence and knowledge with the management of child maltreatment, and that inclusion of mandated child maltreatment training in residency/fellowship and mandated training for medical licensure in all states could improve child maltreatment recognition and reporting.